Perceptions of Elementary School Teacher Education Students on the Use of Wordwall Interactive Media as a Quiz - Zeva Adi Fianto; Sekar Purbarini Kawuryan; Bambang Saptono; Mujinem; Galuh Mentari Putri (Universitas Pendidikan Ganesha, 2024)
The use of interactive media in learning activities provides new innovations in the world of education. This study aims to analyze the perceptions of PGSD students on the use of Wordwall interactive media as quizzes in elementary school social studies education courses. This research is a quantitative type with 50 PGSD (Elementary School Teacher Education). The research method used in this research is the survey method. Data was collected using a 1-5 Likert scale questionnaire. Questionnaires were distributed to students via the Google form. The data obtained from the study were then analyzed using a Likert scale and the results were converted into a student perception classification table. The results of the analysis of the questionnaire distributed to PGSD students showed that the perceptions of PGSD students regarding the use of Wordwall interactive media as quizzes in elementary school social studies education courses were in the